2003
DOI: 10.1007/s00572-003-0224-y
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic and terrestrial mycorrhizas in a lower montane Costa Rican cloud forest

Abstract: The epiphyte community is the most diverse plant community in neotropical cloud forests and its collective biomass can exceed that of the terrestrial shrubs and herbs. However, little is known about the role of mycorrhizas in this community. We assessed the mycorrhizal status of epiphytic (Araceae, Clusiaceae, Ericaceae, and Piperaceae) and terrestrial (Clusiaceae, Ericaceae) plants in a lower montane cloud forest in Costa Rica. Arbuscular mycorrhizas were observed in taxa from Araceae and Clusiaceae; ericoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 7 publications
3
54
1
1
Order By: Relevance
“…13,no. 3 occurrence of DSE and AMF and suggest that it is common in plant roots in nature (Rains et al 2003, Muthukumar et al 2006, SantosGonzalez et al 2007, Mandyam & Jumpponen 2008, Khidir et al 2010, Yang et al 2010) and some of them suggest that colonization of roots can be interfered by non-mycorrhizal endophytes, especially during the hot season which corresponds to the plant growing season when water availability is low and that a competition between both endophytes during colonization could limit the distribution of AM in dry region (Mandyam & Jumpponen 2008, Khidir et al 2010, Yang et al 2010. This relation has not been clarified yet; therefore, further studies are needed for resolving the existing relations between both fungal endophytes.…”
Section: Discussionmentioning
confidence: 99%
“…13,no. 3 occurrence of DSE and AMF and suggest that it is common in plant roots in nature (Rains et al 2003, Muthukumar et al 2006, SantosGonzalez et al 2007, Mandyam & Jumpponen 2008, Khidir et al 2010, Yang et al 2010) and some of them suggest that colonization of roots can be interfered by non-mycorrhizal endophytes, especially during the hot season which corresponds to the plant growing season when water availability is low and that a competition between both endophytes during colonization could limit the distribution of AM in dry region (Mandyam & Jumpponen 2008, Khidir et al 2010, Yang et al 2010. This relation has not been clarified yet; therefore, further studies are needed for resolving the existing relations between both fungal endophytes.…”
Section: Discussionmentioning
confidence: 99%
“…epiphytes have slower growth rates, accessory structures (e.g. trichomes and velamen), as well as association with insects and microorganisms (Nadkarni 1984, Stewart et al 1995, Kauff et al 2000, Rains et al 2003, Tsavkelova et al 2003, Shefferson et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies suggest that many plant species that are commonly mycorrhizal when they grow terrestrially are inconsistently mycorrhizal when they grow epiphytically (5,6). However, Rains et al (4) found abundant mycorrhizal structures on epiphytic roots indicating a significant mycorrhizal presence (arbuscular and ericoid mycorrhizas) in the canopy of a lower montane cloud forest in Costa Rica. In these previous studies, the morphology of structures in or around the root was used to characterize plants as mycorrhizal or nonmycorrhizal; however, morphology provides a limited resolution to the question of whether or not a plant species is mycorrhizal.…”
mentioning
confidence: 96%
“…Some epiphytes have evolved adaptations that provide efficient access to and retention of nutrients, such as litter-trapping leaf arrangements, slow growth rates, absorbent trichomes, and mycorrhizas (3,4). The results of previous studies suggest that many plant species that are commonly mycorrhizal when they grow terrestrially are inconsistently mycorrhizal when they grow epiphytically (5,6).…”
mentioning
confidence: 99%